POLITICAL LANGUAGE AS A TOOL OF MANIPULATIVE INFLUENCE - Мадрига, Т. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article discusses the essence of the concept of political language and its manipulative possibilities, analyzes the methods of linguistic manipulation of consciousness and manipulative strategies, based on the use of linguistic means. The political language is seen as a tool for the formation, operation and transfer of political information and as an instrument of influence in the process of conquering power, which prompts certain actions or, conversely, inhibits them and even destabilizes them.